Contract Design for Afforestation Programs - Immorlica, Nicole; Li, Wanyi; Lucier, Brendan (AI for Good, 2020)
Trees on farms provide environmental benefits to society and improve agricultural productivity for farmers. We study incentive schemes for afforestation on farms through the lens of contract theory, designing conditional cash transfer schemes that encourage farmers to sustain tree growth. We capture the tree growth process as a Markov chain whose evolution is affected by the agent’s (farmer) actions – e.g., investing costly effort or cutting the tree for firewood. The principal has imperfect information about the agent’s costs and actions taken, and wants to maximize long-run tree survival with minimal payment. We show how to calculate the optimal contract structure in our model: notably, it can involve time-varying payments and may incentivize the agent to join the program but abandon it prematurely.